Leveraging Micro-Stories to Build Engagement, Inclusion, and Neural Networking in Immunology Education - Lukin, Kara (Frontiers in Immunology, 2019)
Storytelling is a highly effective strategy to delivery course content. It can provide real-world contexts and the relevance students desire. Through personal connections to the narrative details, anecdotes facilitate the incorporation of content into pre-existing knowledge and neural networks which enhances retention. In addition, stories can honor students’ diverse backgrounds which builds a sense of belonging and community. In turn, these aspects can drive intrinsic motivation to learn and increase students’ alertness in class and overall engagement in the course. Despite the educational power of stories, there often is not enough time to integrate them into curricula. To address this dilemma, faculty can condense stories into micro-stories which require relatively minimal class time. Many aspects of stories that enhance learning can be leveraged in just a few sentences by focusing on narrative details that engage a variety of cognitive and emotional processes. In particular, the inclusion of multiple sensory descriptions and small details, like locations and names, can provide sufficient context to maintain the value stories provide. Micro-stories can function independently or extend a single theme throughout a course. Presented in this Perspective are examples of micro-stories for concepts in immunology and strategies for developing them. Proposals are made for leveraging micro-stories to enhance student engagement and course community, content retention and retrieval, and satisfaction with immunology courses of all sizes and levels.